16 Extended vte prophylaxis for all – ensuring correct prescirption after major gi oncological resection. (31st October 2017) - Spence, D; Devlin, J; McKie, L; Kennedy, R; McAdam, T
Abstract : Using a single audit process across the 3 General Surgical Units in the Belfast Trust, Northern Ireland, we identified a lack of adequate extended post-op venous-thromboembolism prophylaxis (EVTEP) in patients following major resection for GI malignancies (as recommended by NICE: CG 92 and endorsed by the 3 UK General Surgical Associations – AUGIS, ACPGBI, and GBIHPBA). We identified 2 areas that we felt, with intervention, could bring departmental performance into sync with national recommendations. Lack of knowledge amongst FY1 Doctors of the need for EVTEP. Lack of a Trust-wide policy on EVTEP. Our planned interventions included; 1. Creation of a Trust-wide policy. 2. Delivery of a presentation on EVTEP for junior doctors during departmental induction at each 4 or 6 month rotation. 3. Creation of an electronic fail-safe on the existing electronic discharge letters preventing letter/script being cleared for sending to pharmacy unless EVTEP was addressed. Improvement was to be measured in the form of a re-audit over a further 6 month period once all the suggested changes had been implemented. Due to the length of time it has taken interventions 1 and 3 to be implemented (greater than 1 year) – it has not been feasible to complete the full re-audit of the impact of all three interventions prior to the date of the conference in Liverpool. In the interim we are collecting re-audit data to measure improvement secondary to intervention number 2 which has been rolled out since our original findings in 2016. This data will be collected from the 2 funded units involved as one currently does not have funding allocated for EVTEP. The results from the mini-re-audit will be available for presentation by October 2017 and we anticipate that we will be able to demonstrate an improvement in overall prescription of EVTEP following full re-audit of our interventions.